Beam Steering of an Array Antenna using Tunable Multi Layer Multi Dielectric-High Impedance Surface Reflector (Global Journals of Research in Engineering, 2014)
Beam scanning have found great demand in the field of wireless communication satellite communication radar etc 1 2 These applications are generally covered by phased array antennas 3 where several elements are grouped together in a linear or planar special configuration The radiated beam is determined by the vector addition of the electromagnetic fields radiated by the individual elements Present proposal a novel technique of Tunable Multi Layer Multi Dielectric High Impedance Surface TMMD-HIS is embedded with array antenna making it possible to obtain a beam scanning angle of 40 degree from -20 degree to 20 degree without the need of expensive active components The major advantage of proposed concept is that the array have a negligible mutual coupling between radiating element this is happen because of suppression of surface wave In built phase shifting is provided which reduces the structure size and proportionally cost simulated results showing the effectiveness and compatibility of proposed concept
Keywords: reflection phase; width of patch; gap between patches; height of substrate; operating frequency; band width